Small aperture evanescent‐mode waveguide antenna matched using distributed coupled resonators. Issue 9 (1st April 2013) - Ludlow, P.; Fusco, V.; Goussetis, G.; Zelenchuk, D.E.
Abstract : Presented is a design methodology which permits the application of distributed coupled resonator bandpass filter principles to form wideband small‐aperture evanescent‐mode waveguide antenna designs. This approach permits matching of the complex antenna aperture admittance of an evanescent‐mode open‐ended waveguide to a real impedance generator, and thereby to a coaxial feed probe. A simulated reflection coefficient of < − 10 dB was obtained over a bandwidth of 20%, from 2.0–2.45 GHz, in a 2.58 GHz cutoff waveguide. Dielectric‐filled propagating waveguide and air‐filled evanescent‐mode waveguide sections are used to form the resonators/coupling elements of the antenna's coupled resonator matching sections. Simulated realised gain variation from 3.4–5.0 dBi is observed across the bandwidth. The antenna's maximum aperture dimension is < 0.47 λ0 at the upper operating frequency and so it is suitable for use in a wide angle scanning phased array.